Microbial Metabolism and Community Dynamics in Hydraulic Fracturing Fluids Recovered From Deep Hydrocarbon-Rich Shale - Morono, Yuki; Wishart, Jessie R.; Ito, Motoo; Ijiri, Akira; Hoshino, Tatsuhiko; Torres, Marta; Verba, Circe; Terada, Takeshi; Inagaki, Fumio; Colwell, Frederick S. (Frontiers in Microbiology, 2019)
Hydraulic fracturing is a prominent method of natural gas production that uses injected, high-pressure fluids to fracture low permeability, hydrocarbon rich strata such as shale. Upon completion of a well, the fluid returns to the surface (produced water) and contains natural gas, subsurface constituents, and microorganisms (Barbot et al., 2013, Daley et al., 2016). While the microbial community of the produced fluids has been studied in multiple gas wells, the activity of these microorganisms and their relation to biogeochemical activity is not well understood. In this experiment, we supplemented produced fluid with 13C-labeled carbon sources (glucose, acetate, bicarbonate, methanol, or methane), and 15N-labeled ammonium chloride in order to isotopically trace microbial activity over multiple day in anoxic incubations. Nanoscale secondary ion mass spectrometry (NanoSIMS) was used to generate isotopic images of 13C and 15N incorporation in individual cells, while isotope ratio monitoring – gas chromatography – mass spectrometry (IRM-GC-MS) was used to measure 13CO2, and 13CH4 as metabolic byproducts. Glucose, acetate, and methanol were all assimilated by microorganisms under anoxic conditions. 13CO2 production was only observed with glucose as a substrate indicating that catabolic activity was limited to this condition. The microbial communities observed at 0, 19, and 32 days of incubation did not vary between different carbon sources, were low in diversity, and composed primarily of the class Clostridia. The primary genera detected in the incubations, Halanaerobium and Fusibacter, are known to be adapted to harsh physical and chemical conditions consistent with those that occur in the hydrofracturing environment. This study provides evidence that microorganisms in produced fluid are revivable in laboratory incubations and retained the ability to metabolize added carbon and nitrogen substrates.